Effects of intentionally introduced nitrogen and substrate temperature on growth of diamond bulk single crystals. (17th December 2015) - Yamada, Hideaki; Chayahara, Akiyoshi; Mokuno, Yohiaki
Abstract: Aiming at stable growth of bulk single-crystal diamond, multiple effects of intentional nitrogen introduction and substrate temperature on the growth were studied. The intensity of fluorescence of the nitrogen-vacancy (NV 0 ) center was qualitatively correlated with the concentrations of nitrogen in the grown layers. Growth rates and morphologies varied with nitrogen concentration in the gas phase and substrate temperature. It was shown that appropriate control of substrate temperature allows continuous growth, which makes the substrate thicker. The mechanism underlying the effect of nitrogen on growth rate is discussed on the basis of the obtained results, which suggest also the importance of substrate temperature in controlling migration and the surface reactions of radicals.